Gastrointestinal Parasites in Children and Dogs (Canis lupus familiaris) in Agbarho, Delta State, Nigeria: Prevalence, Intensity, and Seasonal Distribution - Yvonne O Okuma; Patrick O. G. Nmorsi (Darul Yasin Al Sys, 2026)
Intestinal parasitic infections remain a major public health challenge in resource-limited settings, particularly in communities where humans and domestic animals share environments that facilitate parasite transmission. This study aimed to determine the prevalence, infection intensity, and seasonal distribution of intestinal parasites among children and dogs in Ughelli North Local Government Area, Delta State, Nigeria. A cross-sectional design was employed, involving the examination of 200 stool samples from children and 186 fecal samples from dogs using standard parasitological techniques. Among children, 226 parasite infections were recorded because of co-infections, with Ascaris lumbricoides being the most prevalent species (57.9%), followed by Entamoeba coli (24.7%), Entamoeba histolytica (9.7%), Trichuris trichiura (7.0%), and Giardia duodenalis (0.4%). Among dogs, 357 parasite detections were recorded, predominantly comprising Trichuris vulpis (74.7%), Toxocara canis (59.6%), and Ancylostoma caninum (57.5%). Infection intensity was highest for A. lumbricoides in children (22.56 ± 20.23 eggs per gram [EPG]) and T. canis in dogs (38.02 ± 29.25 EPG). Parasite prevalence was higher during the wet season, with transmission peaking between July and August. However, statistical analyses revealed no significant associations among the parasite species examined (p > .05). These findings demonstrate a substantial burden of intestinal parasitic infections, indicating extensive environmental contamination and potential zoonotic overlap between children and dogs. Integrated control measures combining mass deworming, improved sanitation, health education, and coordinated One Health interventions are therefore essential to reduce transmission and the associated disease burden.